A smart prayer rug and a method of operating the same - Johar Akbar, Mohamat Gani; Mohamad Riduwan, Md Nawawi; Musa, Yusup Lada; Burairah, Hussin (2015)
A smart prayer rug comprising a plurality of sensors , a display device and a power switch. The smart prayer rug is divided into a foot region, a knee region and a head region. Further, the plurality of sensors are placed on the foot region , the knee region and the head region. The power switch is configured to provide power to the display device and configured to count number of raka’ah performed by a user. Also, the user triggers the display device to display number of raka’ah performed by the user. Further, a method of operating the smart prayer rug is provided.